2011
DOI: 10.1016/j.bpj.2011.08.047
|View full text |Cite
|
Sign up to set email alerts
|

Roles for Cardiac MyBP-C in Maintaining Myofilament Lattice Rigidity and Prolonging Myosin Cross-Bridge Lifetime

Abstract: We investigated the influence of cardiac myosin binding protein-C (cMyBP-C) and its constitutively unphosphorylated status on the radial and longitudinal stiffnesses of the myofilament lattice in chemically skinned myocardial strips of the following mouse models: nontransgenic (NTG), effective null for cMyBP-C (t/t), wild-type cMyBP-C expressed into t/t (WT(t/t)), and constitutively unphosphorylated cMyBP-C (AllP-(t/t)). We found that the absence of cMyBP-C in the t/t and the unphosphorylated cMyBP-C in the Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 58 publications
(94 reference statements)
3
45
0
Order By: Relevance
“…This result is especially impressive given that mouse tissue lacking MyBP-C used by Stelzer et al 29 also possessed a higher fraction of the slower β-MyHC compared with controls, yet demonstrated faster responses. We have shown that myosin cross-bridge detachment rate is inhibited by MyBP-C 30 ; the inhibition is more potent in β-MyHC than in α-MyHC. 31 Importantly, phosphorylation of MyBP-C by PKA removes its normal inhibition of the rate of force redevelopment 30 and would likewise be expected to enhance acto-myosin cross-bridge detachment rate and myofilament-dependent relaxation.…”
Section: Current Knowledge Of Myosin-bindingmentioning
confidence: 88%
See 1 more Smart Citation
“…This result is especially impressive given that mouse tissue lacking MyBP-C used by Stelzer et al 29 also possessed a higher fraction of the slower β-MyHC compared with controls, yet demonstrated faster responses. We have shown that myosin cross-bridge detachment rate is inhibited by MyBP-C 30 ; the inhibition is more potent in β-MyHC than in α-MyHC. 31 Importantly, phosphorylation of MyBP-C by PKA removes its normal inhibition of the rate of force redevelopment 30 and would likewise be expected to enhance acto-myosin cross-bridge detachment rate and myofilament-dependent relaxation.…”
Section: Current Knowledge Of Myosin-bindingmentioning
confidence: 88%
“…We have shown that myosin cross-bridge detachment rate is inhibited by MyBP-C 30 ; the inhibition is more potent in β-MyHC than in α-MyHC. 31 Importantly, phosphorylation of MyBP-C by PKA removes its normal inhibition of the rate of force redevelopment 30 and would likewise be expected to enhance acto-myosin cross-bridge detachment rate and myofilament-dependent relaxation.…”
Section: Current Knowledge Of Myosin-bindingmentioning
confidence: 88%
“…This effect is likely because of the fact that the presence of cMyBPC imparts an elastic and viscous load on the myosin heads, which acts to slow force relaxation and that absence of cMyBPC leads to a more compliant XB and possibly a greater degree of radial compliance of the sarcomeric lattice55 in the KO myocardium, resulting in an abbreviated XB “ on ” time. Interestingly, our data also show that Myk461 incubation significantly slowed k rel in the KO myocardium but not in the WT myocardium, effectively normalizing the basal differences in k rel between KO and WT groups (Table 3; Figure 5), suggesting a slowing in the strain‐induced XB detachment from actin in the KO myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…However, subsequent PKA treatment significantly increased the phosphorylation of TnI (1.8-fold), titin (1.7-fold), and MyBP-C (1.5-fold). Therefore, phosphorylation of titin, a major modulator of the passive longitudinal stiffness, as well as TnI and MyBP-C, might be involved in muscle relaxation by causing a decrease in the transverse stiffness of myocardial fibers in response to b-AR stimulation under normal physiological conditions (11,12).…”
Section: Short Communicationmentioning
confidence: 99%